Research status and outlook of Android security - Sihan QING (Dianxin kexue)
Currently, Android is the most popular operating system for smartphones. At the same time, its security situation is becoming increasingly serious. The following topics: the development course of Android version updates, the features of Android system, Android security mechanism, analysis of Android security risks, Android malware and attack, and the analysis and defense measures were covered. Finally, the current research status and progress, and the future research directions regarding Android security were addressed.